Social media and the future of open debate: A user-oriented approach to Facebook's filter bubble conundrum. (March 2019) - Seargeant, Philip; Tagg, Caroline
Abstract: Drawing on a two-year project, Creating Facebook, this article explores how the actions and agency of Facebook users contribute to the distortion of information and polarisation of socio-political opinion. Facebook's influence as a channel for the circulation of news has come under intense scrutiny recently, especially with regard to the dissemination of false stories. While this criticism has focused on the 'filter bubbles' created by the site's personalisation algorithms, our research indicates that users' own actions also play a key role in how the site operates as a forum for debate. Our findings show that the strategies people use to navigate the complex social space contribute to the polarising of debate, as they seek to avoid conflict with the diverse members of their network.